Disease Course and Pulmonary Involvement of COVID-19 during the Delta Variant Period in Germany: A Comparative Study of Vaccinated and Unvaccinated Patients at a Tertiary Hospital - Steuwe, Andrea; Ljimani, Alexandra; Andree, Marcel; Wienemann, Tobias; Lübke, Nadine; Walker, Andreas; Jensen, Björn-Erik Ole; Group, The Racoon Study; Radke, Karl Ludger; Antoch, Gerald; Valentin, Birte (Current Medical Imaging, 2024)
Background Despite the availability of vaccines, there is an increasing number of SARS-CoV-2-breakthrough-infections. Objective The aim of this study was to determine whether there is a radiological difference in lung parenchymal involvement between infected vaccinated and unvaccinated patients. Additionally, we aimed to investigate whether vaccination has an impact on the course of illness and the need for intensive care. Methods This study includes all patients undergoing chest computed tomography (CT) or x-ray imaging in case of a proven SARS-CoV-2 infection between September and November 2021. Anonymized CT and x-ray images were reviewed retrospectively and in consensus by two radiologists, applying an internal severity score scheme for CT and x-ray as well as CARE and BRIXIA scores for x-ray. Radiological findings were compared to vaccination status, comorbidities, inpatient course of the patient’s illness and the subjective onset of symptoms. Results In total, 38 patients with acute SARS-CoV-2 infection underwent a CT scan, and 168 patients underwent an x-ray examination during the study period. Of these, 32% were vaccinated in the CT group, and 45% in the x-ray group. For the latter, vaccinated patients exhibited significantly more comorbidities (cardiovascular (p=0.002), haemato-oncological diseases (p=0.016), immunosuppression (p=0.004)), and a higher age (p<0.001). Vaccinated groups showed significantly lower extent of lung involvement (severity scores in CT cohort and x-ray cohort both p≤0.020; ARDS 42% in unvaccinated CT cohort vs. 8% in vaccinated CT cohort). Furthermore, vaccinated patients in the CT cohort had significantly less need for intensive care treatment (p=0.040). Conclusion Our data suggest that vaccination, in the case of breakthrough infection, favours a milder course of illness concerning lung parenchymal involvement and the need for intensive care, despite negative predictors, such as immunosuppression or other pre-existing conditions.
Keywords: ARDS